A flexible Li-ion battery with design towards electrodes electrical insulation. (22nd July 2016) - Vieira, E M F; Ribeiro, J F; Sousa, R; Correia, J H; Goncalves, L M
Abstract: The application of micro electromechanical systems (MEMS) technology in several consumer electronics leads to the development of micro/nano power sources with high power and MEMS integration possibility. This work presents the fabrication of a flexible solid-state Li-ion battery (LIB) ( 2.1 μ m thick) with a design towards electrodes electrical insulation, using conventional, low cost and compatible MEMS fabrication processes. Kapton ® substrate provides flexibility to the battery. E-beam deposited 300 nm thick Ge anode was coupled with LiCoO2 /LiPON (cathode/solid-state electrolyte) in a battery system. LiCoO2 and LiPON films were deposited by RF-sputtering with a power source of 120 W and 100 W, respectively. LiCoO2 film was annealed at 400 °C after deposition. The new design includes Si3 N4 and LiPO thin-films, providing electrode electrical insulation and a battery chemical stability safeguard, respectively. Microstructure and battery performance were investigated by scanning electron microscopy, electric resistivity and electrochemical measurements (open circuit potential, charge/discharge cycles and electrochemical impedance spectroscopy). A rechargeable thin-film and lightweight flexible LIB using MEMS processing compatible materials and techniques is reported.